Sensory evaluation and consumer acceptability of novel fortified blended foods - Chanadang, Sirichat (Kansas State University, 2017)
Fortified blended foods (FBFs), which are the mixture of cereals and legumes fortified with micronutrients, have been widely used as supplementary foods for vulnerable populations such as infants and young children in developing countries around the world. The evaluation of current FBFs showed limited evidence on their effectiveness in treating childhood malnutrition, resulting the several recommendations on processing and formulation changes to improve their quality and ability to meet nutritional needs. Sensory properties are one of the important determinants for the success of the new FBFs. Therefore, sensory testing was conducted to determine the potential of novel FBFs to be used as supplementary food compared with FBF currently used in food aid programs. Descriptive sensory analysis was performed on novel FBFs along with the traditional FBF (Corn soy blend plus; CSB+) to determine sensory characteristics of each FBF. Results showed that novel FBFs had more pronounced toasted characteristics and higher sweetness than CSB+, due to the higher temperature during extrusion process and the addition of sugar in the novel formulation. In addition, novel FBFs that had higher amount of legumes (e.g. soybean, cowpea) in their formulations, especially for all sorghum cowpea blends, showed higher intensity in beany characteristics. Sensory shelf-life testing showed that novel FBFs could have shelf lives at least 2 years with no detection of off-note characteristics and these was comparable to the shelf life of the current FBF (CSB+). Sensory testing was also performed with target populations: children who eat the food and care givers who prepare it, during a 20-week field trial to determine the acceptability and preference of novel FBFs and current FBF. Results showed that all novel FBFs were highly preferred or accepted by children, even though, some of them might need longer time and more exposures to allow children to have more experience and be familiar with the food before being satisfied or preferred that food. In contrary, CSB+ that had bland flavor tended not to be well accepted and highly preferred by children compared to novel FBFs. Moreover, giving children more opportunities to consumed food prepared from CSB+ did not help to improve its acceptability or preference. Data from household visits and interview sessions showed that porridges prepared from novel FBFs required less cooking time than CSB+ and no additional ingredients needed to be added compared to CSB+ where sugar and milk were common additions. Finding from this research indicated that novel FBFs have high potential to be used successfully as supplementary food with comparable shelf life, and higher acceptability and preference to FBF currently used in food aid programs. In addition, the simple cooking of novel FBFs make them valuable to caregivers who have limited time and access to energy sources and nutrient-rich ingredients.
Keywords: Sensory Analysis; Consumer test; Acceptability; Field trial; Fortified Blended Foods (FBFs)